Animal models of anxiety and benzodiazepine actions. - Iversen, S (1980)
If rats trained to press a lever for food, then receive a shock to the feet following every response, their behavioural output is severely depressed. This procedure is termed immediately punishment and it was used by Geller and Seifter in the task devised to demonstrate the anxiolytic effect of benzodiazepines. These drugs and a number of others with anxiolytic activity (e. g. barbiturates, ethanol) reverse the suppression induced by the presentation of a highly aversive stimulus, like electric shock. The Geller-Seifter procedure has figured prominently in behavioural studies of benzodiazepines and in the efforts to determine the neuropharmacological basis of their anxiolytic action. Experiments involving the manipulation of brain noradrenaline (NA) and 5-hydroxytryptamine (5-HT) levels with drugs or lesions are discussed. The Geller-Seifter procedure is, however, a time consuming and difficult behavioural baseline to work with. It is important, therefore, to devise equally specific but simpler animal models of anxiety. Electric shock, as the anxiety-inducing event has dominated the tasks devised by behavioural psychologists. It is essential to search for more biologically relevant events with which to control the level of anxiety in experimental animals. Tests involving the manipulation of novelty and uncertainty will be presented and their responsiveness to anxiolytic drugs and neuropharmacological manipulation discussed. Recent advances in defining the biochemical and pharmacological properties of benzodiazepine receptors and particularly of their differential distribution in brain, makes it likely that simple reliable animal tests of anxiety would serve neuropharmacology well and be of great value in understanding the functional importance of the benzodiazepine receptors of brain.